Voices in Videos: How YouTube Is Used in #BLM and #StopAAPIHate Movements - Aanandita Bali; Shuo Niu (Platforms)
Video-sharing platforms have significantly influenced social justice movements by creating unprecedented opportunities for mobilization and support. However, YouTube’s unique role and platform culture in facilitating social justice movements remain relatively understudied. This research addresses this gap by analyzing video content related to two prominent online social justice movements: #BLM and #StopAAPIHate. We conducted a comprehensive thematic analysis of a dataset comprising 489 videos obtained using the YouTube Data API. Thematic categories were developed to explore the identities of video creators, the type of information conveyed, storytelling techniques, and promotional features utilized. Our findings indicate that public figures, vloggers, and news reporters are the most frequent creators of videos supporting these movements. The primary purpose of these videos is to share movement-related knowledge and personal stories of discrimination. Most creators primarily promote their social media accounts and do not extensively utilize platform features such as live streaming, merchandise sales, donation requests, or sponsorships to actively support these social justice initiatives.